2022
DOI: 10.1155/2022/5764800
|View full text |Cite
|
Sign up to set email alerts
|

Improved Fuzzy Algorithm for College Students’ Academic Early Warning

Abstract: The existing fuzzy clustering algorithms are mostly fuzzy comprehensive evaluation algorithms based on specific elements, but the main problem of such fuzzy algorithms is the lack of overall research on the responsible individuals and the lack of hierarchy in the algorithms. It is suitable for data mining of academic early warning systems. Therefore, an improved fuzzy algorithm based on fuzzy performance evaluation based on composite elements is proposed, and it is applied to the performance evaluation system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Taking the amount of editing of the employee performance management file information document by each person in the process of employee performance management file information processing as a rigid indicator, it is calculated that each office employee receives the employee performance management file information from the employee performance management file information in the process of employee performance management file information flow [41,42]. e amount of editing between two employee performance management file information versions (that is, the number of modified characters in the document) for information forwarding the statistics of the editing volume of performance management file information is used as a quantitative reference index in the quantitative calculation of performance evaluation [43,44].…”
Section: Algorithm Function Module Analysismentioning
confidence: 99%
“…Taking the amount of editing of the employee performance management file information document by each person in the process of employee performance management file information processing as a rigid indicator, it is calculated that each office employee receives the employee performance management file information from the employee performance management file information in the process of employee performance management file information flow [41,42]. e amount of editing between two employee performance management file information versions (that is, the number of modified characters in the document) for information forwarding the statistics of the editing volume of performance management file information is used as a quantitative reference index in the quantitative calculation of performance evaluation [43,44].…”
Section: Algorithm Function Module Analysismentioning
confidence: 99%
“…Experiments showed that the SVM early warning model based on improved FOA was superior to the traditional SVM model, decision tree and random forest in accuracy. Chen [15] proposed an improved fuzzy algorithm, based on fuzzy performance evaluation of composite elements, and applied it to a performance evaluation system to solve complex problems in performance evaluation. In the process of building smart campus in universities, academic early warning, as a main component of smart campus, mainly aimed to ensure that students successfully completed their studies using data mining technology, and provided certain decision-making support for universities.…”
Section: Introductionmentioning
confidence: 99%